Estudo de propriedades estruturais, eletrônicas e magnéticas de clusters de Rh13, Pd13 E Pt13 - Piotrowski, Maurício Jeomar (2009)
This work shows a theoretical study of Rh13, Pd13, and Pt13 clusters, using first principles methods. We sought to understand aspects of stability and magnetic moment for these systems. The employed methodology was tested by calculating the structural and electronic properties of bulk Rh, Pd and Pt, by studying the equilibrium lattice constants, bulk modulus, cohesion energies and density of states (DOS). These bulk results also serve as a reference for the study of clusters. To study the properties of clusters we initially search for the atomic structures of minimum energy for these systems. We implement a strategy to obtain the clusters structures which is based on high-temperature molecular dynamics calculations. This search was complemented by the addition high-symmetry structures or structures with similarity to those already proposed in the literature. We obtained among 25 and 40 structures for each of the Rh13, Pd13 and Pt13 clusters. For Rh13 and Pd13 we find for the ground state the same structures reported in the literature, but for Pt13 a new lowest energy structure was found. The resulting set of clusters, including ground state and higher energy structures show characteristic patterns as: (i) packed structures, (ii) open cubic-like structures, (iii) layered structures and (iv) low symmetry structures. The structures obtained as the most stable for Rh13, Pd13 and Pt13 show that the increasing importance of d states for the binding of clusters leads to structures with low symmetry and small packing factors. The obtained magnetic moment values are excellent agreement with literature, with a nonlinear dependence on the average bond length. The high density of states at the Fermi level shows both the large magnetic moments and low energetic stability for the clusters, following the Stoner criterion. The decomposition of the DOS shows the large contribution of d levels to the close to Fermi energy, thus confirming a well established feature for transition metals. Positive vibrational frequencies for the whole set of the studied clusters revealed that the obtained structures are local minimum. The analysis of the average bond length, magnetic moment, vibrational frequencies, and effective coordination number show that the obtained structures follow a structural pattern that depends on the occupation of d states valence shell.